Salvia divinorum – A New Entity in the Psychedelic Scene in India (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Salvia divinorum is a psychoactive plant that produces intense hallucinations and is used as a recreational drug increasingly. The Mazatec Indians used it in spiritual healing sessions. The fact that the drug is easily available through the internet and the lack of restrictions on its use in many countries have contributed to its widespread abuse. There have also been reports of drugs being used in India.
Keywords: Salvia divinorum; SalvinorinA; Substance abuse; Hallucinogen